1993
DOI: 10.1080/00332747.1993.11024642
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Treatment Contract in Intensive Psychotherapy with Borderline Patients

Abstract: A pilot study on the process of psychodynamic psychotherapy of borderline personality disorder at the Cornell University Medical College is designed to investigate the teaching and application of a specific model of treatment for borderline patients (Clarkin et al. 1992; Kernberg and Clarkin 1992). The project has involved teaching a group of self-selected trainees and faculty the manualized therapy (Kernberg et al. 1989); taping each of the twice-weekly therapy sessions over a period of 2 years; and rating (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 4 publications
0
32
0
2
Order By: Relevance
“…This diagnostic category of patients is known for being associated with particular difficulties in interpersonal and intimate relationships (APA, 1994;Barnow et al, 2009;Benjamin, 2003;Bohus, 2002;Perry, 2004, 2009;Ruiz et al, 1999;Stern et al, 1997), including in the interaction with the therapist, along with counter-transference issues (Gunderson et al, 1989;Spinhoven et al, 2007;Yeomans et al, 1993). These interpersonal difficulties may partially explain the high level of drop-outs, observed even in modern manual-based treatments.…”
Section: Borderline Personality Disorder: a Case In Pointmentioning
confidence: 92%
See 1 more Smart Citation
“…This diagnostic category of patients is known for being associated with particular difficulties in interpersonal and intimate relationships (APA, 1994;Barnow et al, 2009;Benjamin, 2003;Bohus, 2002;Perry, 2004, 2009;Ruiz et al, 1999;Stern et al, 1997), including in the interaction with the therapist, along with counter-transference issues (Gunderson et al, 1989;Spinhoven et al, 2007;Yeomans et al, 1993). These interpersonal difficulties may partially explain the high level of drop-outs, observed even in modern manual-based treatments.…”
Section: Borderline Personality Disorder: a Case In Pointmentioning
confidence: 92%
“…Specific relational techniques were prescribed by the manuals, such as validation and acceptance in the context of DBT, to enhance the quality of the patient's way of entering the relationship with the therapist (Linehan, 1993;Lieb et al, 2004;Bohus, 2002). Yeomans et al (1993Yeomans et al ( , 2002 proposed, in the context of transference-focused psychotherapy, to focus on the negative contents projected onto the therapist and on the elaboration of a treatment contract starting right at the beginning of treatment. The limitations of these manual-based procedures focusing on relationship stakes have already been cited (Stiles et al, 1998).…”
Section: Borderline Personality Disorder: a Case In Pointmentioning
confidence: 99%
“…Kernberg'in [16] ve Kohut'un [7] geliştirdiği kuramlar psikoanalitik görüşün ilkelerini bu hastalarda kullanmayı olanaklı kılmış, danışan ve terapist arasındaki ilişki-nin öne çıktığı, daha aktif ve kısmen doyuran teknikler geliştirilmiştir. [17][18][19][20][21][22] Bu danışanların psikoterapisinde esas olan, egonun güçlendirilmesi, psikopatolojik nesne ilişkilerinin düzeltilmesi, ilkel savunmalardan daha gelişmiş savunmalara ilerlemenin sağlanmasıdır.…”
Section: Sonlanma Aşamasında Yaşanan Zorluklarunclassified
“…Birçok yazar, ağır kişilik bozukluğu olan kişilerde, ayrılma aşamasında çok çeşitli güçlüklerin ortaya çıktığı konusunda ortak görüşler belirtmektedir. [15,[20][21][22]26] Adler (1981), sınır kişilik bozukluğu gösteren hastaların iyileşme aşama-sında narsisistik bir yapı sergilediklerini, Waldinger (1984), genel eğilimlerinin, tedaviyi aşağılayarak ve olumsuz bir yaşantı ile bitirmeleri yönünde olduğunu belirtmektedir. [26,27] Bu durum, ağır kişilik bozukluğu gösteren kişilerin ayrılığa ve kayba ancak olumsuz bir yaşantı ile -değersizleştirerek-tahammül edebildiklerini göstermektedir.…”
Section: Sonlanma Aşamasında Yaşanan Zorluklarunclassified
“…Yeomans, Seizer and Clarkin (1993) studied the application of treatment contracting with borderline patients as a component of intensive outpatient psychodynamic therapy. They found that the quality of the contract, therapist implementation skills, and patient collaboration (regarding goal-setting and patient acceptance of the contract) had a positive effect in reducing patient dropout rate.…”
Section: Patient Collaborationmentioning
confidence: 99%